The Village Empowerment Through Circular and Green Economic Programs Through Independent Waste Management - Ratri, Wahyu Setya; Astuti, Ari; Permatasari, Desy Ayu Irma (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Tofu and organic waste are problems that are high on the agenda in Yogyakarta, especially in Sleman and Bantul. This area is also the largest center of the tofu industry and essential oil from red lemongrass in DIY. Through the Community Service (Abdimas) program in collaboration with Rumah Maggot Barepan Bangkit (RMBB) and the Sereh Merah Farmer Group in the Integrated Community Service Program program with MBKM Based on IKU for Private Universities in 2022-2023 in collaboration with the Directorate of Research, Technology, and Community Service Kemdikbudristek, UST Faculty of Agriculture and Faculty of Pharmacy Duta Bangsa University, try to empower the community with circular and green economiy activities the waste becomes money. This activity aims to increase the capacity of the community to become an independent waste processing center, teaching the processing of lemongrass leaves into fertilizer, processing maggot into pellets, processing and packaging kasgot into fertilizer and planting media. This service is divided into three stages, taking place from 2022 - 2023. The activities are divided into three stages. The first stage is socialization of independent lemongrass waste management, introduction of soil improver factors, and processing maggot into pellets.The second stage is a workshop on making POC and biofertilizer made from lemongrass, processing maggot into pellets, processing kasgot into fertilizer and planting media.The third stage is practice and application, making biofertilizer, POC, and floating pellets in the two fostered communities. It is hoped that this service will create a circular economy where the community can manage waste independently, get benefits from waste management and economic turnover in the village. In addition, it will create a green economy, where there is no more waste generated from the activity and the waste becomes money.